The fertilizer source conditions the yield and quality of ‘Hass’ avocado fruits - García-Martínez, René; Cortés-Flores, José Isabel; López-Jiménez, Alfredo; Etchevers-Barra, Jorge D.; Carrillo-Salazar, José Alfredo (Revista Mexicana de Ciencias Agrícolas, 2025)
Optimal nutrition of fruit trees is critical to obtaining high yields of quality fruit for the fresh fruit market. Producers apply different types of fertilizers in the management of ‘Hass’ avocados, which generates differences in production. Therefore, this work aimed to study the response of the yield and quality of ‘Hass’ avocado fruits to the fertilization source. An experiment was established in an eight-year-old ‘Hass’ avocado orchard in Villa de Allende, State of Mexico. In 2018 and 2019, four sources of fertilizer applied to the soil were studied: control, organic, mineral, and combined. Yield (kg tree-1), number, individual weight and size of the fruits were measured. To evaluate the postharvest behavior, the fruits were stored for nine days at 22 °C and 90% RH. In this period, dry matter content, cumulative weight loss, firmness, and color were measured. Organic fertilizer led to a higher yield (kg tree-1) and number of fruits. Dry matter content (23.3%) and weight loss (9%) did not differ between treatments. At maturity of consumption, the firmness of the fruits of the mineral source was superior to the control. The hue angle of the exocarp in the fruits of the combined source was similar to the control. In general, the fruits of the mineral and organic sources developed better external color. In conclusion, the application of organic fertilizer improved fruit yield, whereas with the mineral source, the fruits were superior in quality and postharvest behavior.